Diphtheria rare localization in adults - Yu. I. Liashenko; Yu. P. Finogeev; D. A. Pavlovich (Журнал инфектологии)
Last 25 years in the country established sporadic diphtheria morbidity (less than 0.1 per 100 000 people). In this situation, the attention of medical specialists pre-hospital and hospital health care system is reduced, especially for diseases with a rare localization of pathological process. Mentioned circumstances contribute to delayed diagnosis and treatment of his patients, the major cause of complicated infection, often its unfavorable outcome and a factor of the epidemic of trouble for the infection. The authors present material evidence that the rare forms of diphtheria in the period of sporadic disease in much the same as in the epidemic, and describe the clinical manifestations and course of diphtheria of the nose, eyes, throat, genitals, mouth and gastrointestinal tract in modern conditions.